Lymphomatoid Granulomatosis Treated Successfully with Rituximab in a Renal Transplant Patient - El Haggan, Wael; Castrale, Cindy; Chapon, Françoise; Reman, Oumedaly; Lobbedez, Thierry; Ryckelynck, Jean Philippe; Hurault de Ligny, Bruno (Journal of Transplantation, 2011)
Lymphomatoid granulomatosis (LYG) in renal transplant recipients is rare multisystemic angiocentric lymphoproliferative disorder with significant malignant potential. Here, we describe LYG in a 70-year-old renal allograft recipient who, 4 years after transplantation, on tacrolimus and mycophenolate mofetil and prednisone maintenance immunosuppression, complained of low-grade fever, persistent headache and gait disturbance. The MRI of the brain revealed diffuse periventricular cerebral and cerebellar contrast-enhanced lesions. The CT scan of the thorax showed multiple pulmonary nodular opacities in both lung fields. The patient was diagnosed LYG based on the cerebral biopsy showing perivascular infiltration of CD20-positive B-lymphocytes with granulomatous lesions and immunofluorescence staining with anti-EBV antibodies. With careful reduction of the immunossuppression combined with the use of rituximab, our patient showed a complete disappearance of LYG, and she is clinically well more than 4 years after the diagnosis, with good kidney function. No recurrence has been observed by radiological imaging until now. This is the first report of a durable (>4 years) complete remission of LYG after treatment with rituximab in renal transplantation.